Self-Access Language Learning in Museums: A Materials Development Project. - Richard Pemberton; Lucy Cooker (Studies in Self-Access Learning Journal, 2010)
This paper reports on a project carried out at The University of Nottingham to create and evaluate English for Speakers of Other Languages (ESOL) materials with the aim of exploiting the self-access language learning possibilities that museums offer. A series of thematic resources were produced and trialed with ESOL learners in the Lincolnshire area. Feedback from the learners indicated that museums could have an important role to play in providing flexible language learning opportunities for ESOL students. The authors conclude by suggesting that other public facilities such as libraries, art galleries, botanical gardens and even football stadia could be exploited for this purpose.